Pembelajaran Komputer Dasar Untuk Siswa Kelas 5 di SDN 1 Cempaka - Ade Johar Maturidi; Della Hanif Abdila; Risa Halimatusya'diyah (LPPM POLITEKNIK LP3I, 2024)
The contents of this report summarize the author's experiences and contributions during the implementation of analyzing activities in Cempaka Village, Talun District, Cirebon City. This KKN activity is a representation of students' commitment to society through providing empowerment support, training and counseling which was carried out for about one month, from 15 July to 19 August 2023. This report describes the author's responsibilities and personal journey in various community service activities. z. We as KKN students carry out our responsibility to provide community service, one of which is by providing basic computer training to students at SDN 1 Cempaka. Technology is increasingly developing and the use of technology must be introduced to students as early as possible with the aim of making students know and learn more about computers.